2020
DOI: 10.1002/bse.2685
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable manufacturing and green human resources: Critical success factors in the automotive sector

Abstract: This study aims to identify critical success factors (CSFs) for implementing sustainability in organizational human resources management (OHRM) within the automotive sector (AS). A literature review was carried out to identify the OHRM factors that are instrumental for the significant adoption of sustainable practices (SP) in the sector. Based on the outcomes from the literature review, an expert team composed of 17 experts from the AS, academia, and consultancy firms were consulted in order to identify cause–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Furthermore, the resource‐based theory supports this finding (Barney, 1991; Barney et al, 2011), in which top management commitment is viewed as a crucial internal organisational source for implementing environmental practices (Dai et al, 2015). These results are consistent with earlier studies, which found that top management commitment influenced the adoption of the ISO 14001 environmental management system (Chiarini, 2019), green HRM (Obeidat et al, 2018; Yusliza et al, 2019), sustainable practices (Gedam et al, 2021), and green procurement (Liu et al, 2020). The relationship between each green HRM practice and top management commitment is discussed in detail below.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the resource‐based theory supports this finding (Barney, 1991; Barney et al, 2011), in which top management commitment is viewed as a crucial internal organisational source for implementing environmental practices (Dai et al, 2015). These results are consistent with earlier studies, which found that top management commitment influenced the adoption of the ISO 14001 environmental management system (Chiarini, 2019), green HRM (Obeidat et al, 2018; Yusliza et al, 2019), sustainable practices (Gedam et al, 2021), and green procurement (Liu et al, 2020). The relationship between each green HRM practice and top management commitment is discussed in detail below.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous studies of green practices, top management commitment is required to create an efficient ISO 14001 environmental management system (Chiarini, 2019), adopt sustainable practices (Gedam et al, 2021), engage in green procurement (Liu et al, 2020), and green HRM (Yusliza et al, 2019). 2019) highlighted that top management involvement is critical in adopting green HRM practices to create a positive environmental performance.…”
Section: Top Management Commitment and Green Hrmmentioning
confidence: 99%
See 2 more Smart Citations
“…The study (Chaudhary, 2020;Gedam et al, 2021;Song et al, 2020) holds that stakeholders of manufacturing plants are responsible for technology development for green and eco-friendly solutions. Scholars observe that CSFs like commitment from top, greening of activities with the support of employees and suppliers' involvement are important.…”
Section: Stakeholders' Involvement and Commitment For Gm (Sic = E 1 )mentioning
confidence: 99%